2018
DOI: 10.21873/invivo.11355
|View full text |Cite
|
Sign up to set email alerts
|

Bufalin Enhances Immune Responses in Leukemic Mice Through Enhancing Phagocytosis of MacrophageIn Vivo

Abstract: Bufalin increased immune responses by enhancing phagocytosis in mice with leukemia mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Our previous findings have shown that bufalin caused apoptotic cell death in human nasopharyngeal carcinoma cells (24) and against lung cancer xenograft animals in vivo (25). Furthermore, we also found that bufalin promoted phagocytosis of macrophages in peripheral blood and the peritoneal cavity in leukemia mice in vivo (26).…”
supporting
confidence: 55%
“…Our previous findings have shown that bufalin caused apoptotic cell death in human nasopharyngeal carcinoma cells (24) and against lung cancer xenograft animals in vivo (25). Furthermore, we also found that bufalin promoted phagocytosis of macrophages in peripheral blood and the peritoneal cavity in leukemia mice in vivo (26).…”
supporting
confidence: 55%
“…YUNG‐LUEN SHIH and colleagues found that bufalin increased the body weight, but reduced liver and spleen weights, and reduced CD3, CD16 and Mac‐3 cell markers. They finally conclude that bufalin may modulate immune responses not only through increasing monocyte (CD11b) population and T‐ and B‐cell proliferation, but also by increasing macrophage phagocytosis in leukaemic mice in vivo 42 . Marco Busnelli and colleagues found that fenretinide, a synthetic retinoid derivative, could induce spleen abnormally enlarged and markedly increased atherosclerotic lesions at the aortic arch, thoracic and abdominal aorta of fenretinide‐treated mice, just the similar results in our control (western diet) group 43 .…”
Section: Discussionmentioning
confidence: 96%
“…[ 61 ]. The research group of Shih et al also presented a study of a bufadienolide bufalin, which affected the immune system of mice comparably to ouabain [ 62 ]. Bufalin was also described to inhibit hepatocellular carcinoma (HCC) proliferation and migration.…”
Section: Immunomodulatory Action Of Cgs In Cancer Treatmentmentioning
confidence: 99%